Escape behaviour of birds in urban parks and cemeteries across Europe: Evidence of behavioural adaptation to human activity - Morelli, Federico; Mikula, Peter; Benedetti, Yanina; Bussière, Raphaël; Jerzak, Leszek; Tryjanowski, Piotr (The Science of the total environment, 2018)
Urban environments are very heterogeneous, and birds living in the proximity of humans have to adapt to local conditions, e.g. by changing their behavioural response to potential predators. In this study, we tested whether the escape distance of birds (measured as flight initiation distance; FID) differed between parks and cemeteries, areas characterized by different microhabitat conditions and human conduct, that are determinants of animal behaviour at large spatial scales. While escape behaviour of park populations of birds was often examined, cemetery populations have not been studied to the same extent and a large-scale comparison is still missing. Overall, we collected 2139 FID estimates for 44 bird species recorded in 79 parks and 90 cemeteries in four European countries: Czech Republic, France, Italy and Poland. Mixed model procedure was applied to study escape behaviour in relation to type of area (park or cemetery), environmental characteristics (area size, coverage by trees, shrubs, grass, chapels, tombstones, flowerbeds, number of street lamps) and human activity (human density, pedestrians speed and ratio of men/women). Birds allowed people closer in cemeteries than in parks in all countries. This pattern was persistent even when focusing on intraspecific differences in FID between populations of the most common bird species. Escape distance of birds was negatively correlated with the size of parks/cemeteries, while positively associated with tombstone coverage and human density in both types of habitat. Our findings highlight the ability of birds to adapt their behaviour to different types of urban areas, based on local environmental conditions, including the character of human-bird interactions. Our results also suggest that this behavioural pattern may be widespread across urban landscapes.
Keywords: Human Activities; ptáci; chování zvířat; Humans; Birds; Parks, Recreational; veřejné parky; hřbitovy; Ecosystem; Environmental Monitoring; Human disturbance; Urban habitat; lidské činnosti; Cemeteries; Pedestrians speed; lidé; zvířata; Europe; Flight initiation distance; Bird species; monitorování životního prostředí; Graveyard; Animals; Behavior, Animal; Evropa; ekosystém